2018
DOI: 10.1007/s40279-018-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity Interventions on Glycosylated Haemoglobin (HbA1c) in Non-diabetic Populations: A Systematic Review and Meta-analysis

Abstract: PROSPERO CRD42016050991.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
0
17
2
1
Order By: Relevance
“…46 Another systematic review and meta-analysis supported a decrease in HbA1c levels in favor of the physically active group (effect size 0.32; 95% CI 0.01 to 0.62) noting substantial heterogeneity (I 2 =63.2%; p=0.008). 48 Our MR analysis found no effect of average PA, vigorous PA and SB on glycemic traits. This seems plausible because it is unlikely that PA will have a significant effect on these glycemic traits in the normal range in non-diabetic individuals.…”
Section: Discussionmentioning
confidence: 54%
“…46 Another systematic review and meta-analysis supported a decrease in HbA1c levels in favor of the physically active group (effect size 0.32; 95% CI 0.01 to 0.62) noting substantial heterogeneity (I 2 =63.2%; p=0.008). 48 Our MR analysis found no effect of average PA, vigorous PA and SB on glycemic traits. This seems plausible because it is unlikely that PA will have a significant effect on these glycemic traits in the normal range in non-diabetic individuals.…”
Section: Discussionmentioning
confidence: 54%
“…Low number of daily step counts have been associated with all-cause mortality in some longitudinal studies 41 and results from pooled population studies show clear dose-response effects of PA to overall mortality. 42 In patients with type 2 diabetes, several studies have now shown that increasing step counts can significantly decrease HbA1c levels. For instance, a 10 000 steps per day walking prescription increased steps and decreased HbA1c in patients with type 2 diabetes.…”
Section: Pa Measurementioning
confidence: 99%
“…On the other hand, exercise is an efficacious non-pharmacological intervention for type 2 diabetes [12]. Even in non-diabetic subjects, physical activity interventions are associated with reduced HbA1c [13]. We have recently shown that acute bouts of aerobic or combined (aerobic and resistance) exercise can reduce glucose variability in patients with type 2 diabetes [14-15].…”
Section: Introductionmentioning
confidence: 99%